PEMBERDAYAAN KAUM PEREMPUAN DALAM MEMPERKUAT EKONOMI KELUARGA MELALUI BAZAR UMKM DI DESA TANJUNG MEDANG KECAMATAN KELEKAR KABUPATEN MUARA ENIM - Salsabila Irawan; Ayu Wulandari; Tariza Apryandi; Juwita Sari; Ayu Sulastri; Sri Wahyuni; Cecilia Agustin; Maulani Maulani (CV. Denasya Smart Publisher, 2026)
Women's empowerment is an important strategy for improving family welfare, particularly in rural areas. Women's involvement in productive economic activities, such as Micro, Small, and Medium Enterprises (MSMEs), can significantly contribute to household income. This study aims to analyze the role of women's empowerment in strengthening the family economy through MSME bazaar activities in Tanjung Medang Village, Kelekar District, Muara Enim Regency. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of female MSME owners, village officials, and parties involved in organizing the bazaar. Data analysis was conducted descriptively to describe the empowerment process, forms of participation, and their impact on the family economy. The results show that MSME bazaar activities provide a space for women to develop skills, increase self-confidence, and expand marketing networks. Women's active participation in the bazaar has an impact on increasing family income, economic independence, and contributions to the village economy. In addition, support from the village government and collaboration between business actors also strengthen the sustainability of the program. Thus, women's empowerment through MSME bazaars has proven to be an effective way to strengthen family economy and promote local economic development. Continued support in the form of training, access to capital, and promotion is needed for this empowerment program to develop optimally